1997
DOI: 10.1073/pnas.94.26.14900
|View full text |Cite
|
Sign up to set email alerts
|

Ancient mtDNA sequences in the human nuclear genome: A potential source of errors in identifying pathogenic mutations

Abstract: Nuclear-localized mtDNA pseudogenes might explain a recent report describing a heteroplasmic mtDNA molecule containing five linked missense mutations dispersed over the contiguous mtDNA CO1 and CO2 genes in Alzheimer's disease (AD) patients. To test this hypothesis, we have used the PCR primers utilized in the original report to amplify CO1 and CO2 sequences from two independent °( mtDNA-less) cell lines. CO1 and CO2 sequences amplified from both of the °cells, demonstrating that these sequences are also prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(130 citation statements)
references
References 38 publications
5
113
1
7
Order By: Relevance
“…Three points can be made about the library of macaque numts. First, some numts are interspersed within extant macaque mtDNA haplotypes, indicating that numt formation is an ongoing process as has been noted previously (3). Second, no macaque numts clustered with mitochondrial haplotypes of the Cercocebus, Cercopithecus, Mandrillus, Colobus, Papio, or Homo͞Pan lineages, which is consistent with the enormity of sequence space and the fact that mtDNA is fixing mutations faster than numts (7).…”
Section: Resultssupporting
confidence: 65%
“…Three points can be made about the library of macaque numts. First, some numts are interspersed within extant macaque mtDNA haplotypes, indicating that numt formation is an ongoing process as has been noted previously (3). Second, no macaque numts clustered with mitochondrial haplotypes of the Cercocebus, Cercopithecus, Mandrillus, Colobus, Papio, or Homo͞Pan lineages, which is consistent with the enormity of sequence space and the fact that mtDNA is fixing mutations faster than numts (7).…”
Section: Resultssupporting
confidence: 65%
“…[23][24][25][26][27][28] And although heteroplasmic mutations were found in platelets from patients with Alzheimer's disease, 29 this was later found to be an artifact produced by pseudogenes from the nuclear genome. [30][31][32] Although increased levels of deletion in brains postmortem were reported, again this was not confirmed in subsequent studies. 16 Mitochondrial dysfunction has also been implicated in other neurodegenerative disorders such as ALS Molecular Psychiatry (amyotrophic lateral sclerosis) 5 and Huntington's disease.…”
Section: Neurodegenerative Disordersmentioning
confidence: 51%
“…Contamination by nuclear genes needs to be considered when heteroplasmic mutations are examined. [30][31][32] Fifthly, the mtDNA polymorphism is a non-specific genetic risk factor. Recently, it has been suggested that depressive symptoms are elevated in the preclinical phase of Alzheimer's disease 123 and patients with mood disorders have a higher risk of dementia.…”
Section: Methodological Problemsmentioning
confidence: 99%
“…The other possible mechanism is recombination of mtDNA into the nucleus. In several species, including human, chimpanzee and cats (Felis), mitochondrial genes have been incorporated into the nuclear genome, known as Numt DNA (Lopez et al, 1994;Wallace et al, 1997). Usually Numts have acted as pseudogenes in 679,362,207,15 604,362,207,15 HaeIII 689,357,144,63,10 614,357,144,63,10 HapII 685,229,349 610,229,349 HincII 669,594 669,519 TaqI 799,464 724,464 Figure 2 Paternal inheritance of mtDNA in sheep X Zhao et al nuclear genome, but there is a possibility of interaction between nuclear and mitochondrial DNA, and it is conceivable that Numts could be transferred back to the mtDNA.…”
Section: Discussionmentioning
confidence: 99%